Abnormal sympathetic functioning is linked to familial hypertension in nonathletic young males - Jayesh Dalpatbhai Solanki; Ajay P Kapadiya; Hemant B Mehta; Chinmay J Shah (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Sympathetic overactivity mediates abnormal cardiovascular outcome that is affected by stress, lack of physical activity (PA), and familial hypertension (HTN). It can be assessed by blood pressure-based sympathetic function tests. OBJECTIVE: We studied sympathetic function tests in young nonathletic males in relation to measures of obesity, PA, and familial HTN. METHODOLOGY: We recruited 100 males (mean age: 19 years) and measured body mass index (BMI) and body composition parameters by tetrapolar bioelectrical impedance such as total body fat, visceral fat, subcutaneous fat, and skeletal muscle mass. Using instrument cardiac autonomic neuropathy system of Recorders and Medicare System Company, India, blood pressures (supine, standing, and post hand grip) were recorded and studied quantitatively and qualitatively. RESULTS: Physically active and inactive individuals (n = 50 each) had comparable age, BMI, measures of obesity, and sympathetic function tests. However, individuals with familial HTN (n = 37) showed significantly higher obesity measures and blood pressures (supine: systolic blood pressure [SBP] - 133 vs. 115 and diastolic blood pressure [DBP] - 79 vs. 76; standing: SBP - 136 vs. 122 and DBP - 80 vs. 76; post hand grip: SBP - 136 vs. 125 and DBP - 86 vs. 81). Qualitatively, postural hypotension was seen in only two individuals, while worst grading was in post hand grip test significantly and more so in physically inactive group (30%, 28%, and 42% vs. 16%, 20%, and 64%) and individuals with positive familial HTN (32%, 38%, and 30% vs. 17%, 13%, and 70%). CONCLUSION: Familial HTN, but not physical inactivity, affects sympathetic functioning in nonathletic young male medical personnel. It asks for other lifestyle modifications for better cardiovascular health as primary prevention.